GAYA KOMUNIKASI CAPRES JOKO WIDODO DAN PRABOWO SUBIANTO PADA PILPRES 2014 - Riswandi Riswandi (Jurnal Ilmu Komunikasi Acta Diurna, 2017)
Style of communication sometimes can be more important than the content (content) ofcommunication. Many people who understand the content well, but not until the communicationmessage is received or not others because of the inability to convey the message properly. In thecontext of the organization of the state, in order to create a quality relationships between cabinetand people in general to the president, the president needs to develop specific communicationstyles that are part of the character of his personality so that it can contribute to the effectivenessof his administration. The issue to be observed is how the communication style tendencies Jokowiand Prabowo as a presidential candidate in the 2014 presidential election and the communicationstyle based on whether they can be examined personality traits. Norton suggests ten style ofcommunication that is dominant, dramatic, animated expressive, open, argumentative, relaxed,friendly, precise and leaving an impression. Tubbs and Moss mentions six communication stylethat is the controlling style, the equalitarian style, the structuring style, the dynamic style, and thewithdrawal style. Another concept that is relevant to the problem is the personality, whichaccording to experts, there are four individual personality that includes melancholy, Solaris,phlegmatic, and sanguine. The study states that the communication style tends Jokowi tendphlegmatic relaxed personality, whereas Prabowo communication style tends to dramaticpersonality tends Solaris.